A Research Adventure (2009)
Fredy Gonzalo Restrepo Moncada, mentor of the hotbed of research for school students Robotics III: “In May 2009 I decided to embark on the adventure of EAFIT hotbeds of research, together with two of my colleagues and best friends. Full of doubts and expectations, we hoped to take advantage of a unique and interesting possibility. So the journey began. "